Caracterización morfológica e identificación de zonas potenciales de conservación de motilón (Hyeronima alchorneoides) en los siete transectos del proyecto banco de germoplasma - Agualongo Caguana, Emma Estefania (2016)
The present research work Morphological Characterization and Identification of Potential Areas of Conservation of Motilon (Hyeronima alchorneoides), performed with the purpose of characterize morphologically the species arboreal in order to identify the potential areas of conservation into the transects of the Project of Banco de Germoplasma, which are located in La Esperanza and La Maná Parishes of the Cotopaxi Province. It was found the presence of the tree in 3 of the 7 transects in which we collected 9 samples, which were identified 3 individuals per transect for which were 26 variables, 20 qualitative to perform a statistical analysis percentage and 6 quantitative which has prepared an analysis of the data the same, in addition we conducted two multivariate analyses, one with all variables and another with principal components finally produced a dendograma in order to observe the existence of morphological variability between samples.